The Recording, Investigation and Analysis of Accidents at Work (RIAAT) process - Jacinto, C.; Soares, C. G.; Fialho, T.; Silva, S. A. (Policy and Practice in Health and Safety, 2011)
This paper describes the Recording, Investigation and Analysis of Accidents at Work (Registo, Investigacao e Analise de Acidentes de Trabalho — RIAAT) process and illustrates its application to a real accident. The process constitutes a holistic approach to deal with occupational accident information; as such, it merges the several ‘bits’ and ‘parts’ of traditional approaches into a distinctive ‘single process’. The process covers the full cycle of accident information by recording the event and its main circumstances; carrying out an investigation and causal analysis in a multi-layered fashion; producing a plan of action; and setting out activities required for sharing information and promoting organisational learning. The process is contained in a standard form (the main instrument) and a small user’s manual. This procedure is intended for application in small and medium-sized enterprises, and the principal targeted users are occupational safety and health practitioners. The analytical framework includes an accident causation model, which is embedded in the form itself and facilitates application. The methodology for developing the process is based on empirical and theoretical foundations within three main categories: the identification of existing good practices; the legal requirements for employers; and a scientific background of accident modelling, inspired by leading researchers in the domain. The tool described here is now fully developed and its final version (available online in English and Portuguese) was adopted as standard procedure in a couple of organisations during the course of 2010. Some other organisations are currently using it on a trial basis. Future work will include some tailored studies to ascertain usefulness and applicability issues, as well as an inter-analyst validation study.